Effect of drying on antioxidant capacity, sugar content, water content, physical and organoleptic properties of dried candied Dewandaru fruit (Eugeia uniflora L.). Issue 1 (May 2021) - Asri, N K T; Devi, M; Soekopitojo, S
Abstract: Dewandaru fruit is a fruit that has many benefits for health. It's distinctive characteristics make Dewandaru fruit suitable for use as food products in the form of dried sweets. This research is an experimental study using RAL to analyze chemical properties, physical properties and organoeptic properties of dried candied from dewandaru fruits with 4 treatments, drying time for 6 hours, 7 hours, 8 hours and 9 hours with 2 repetitions. The data obtained will be analyzed using One Way ANOVA followed byDMRT further test. The results showed that 9 hours of drying time had the highest chemical properties, namely the antioxidant capacity of 71.49 ppm, sugar content of 47.70 g / 100 grams and water content 35, 33 gr / 100 gram, the highest physical properties were at the reddish level (a +) which was 18.53 but low at the level of brightness (L), namely 9.23 and the yellow level (b +), 57. While the physical properties of the texture of the 9 hour drying time had the highest yield, namely 0.1 Kg / cm2. The highest score for organoleptic properties were taste with 8 hours of drying time, color with 6 hours of drying time, aroma with 6 hours of drying time and no difference in texture.